Analisis Faktor yang Berhubungan dengan Computer Vision Syndrome pada Mahasiswa Kesehatan Masyarakat Universitas Muhammadiyah Surakarta - Khalisha Ramdhani Santoso; Salsabila Purnamasari (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Computer Vision Syndrome (CVS) has become a problem of visual discomfort that might impair a person's physical ability, mental health, and quality of life. The symptoms frequently occur due to a variety of inappropriate factors from the individual, environment, and Visual Display Terminal (VDT). Undergraduate students, as a productive age group with a strong link with VDT usage, are at high risk of developing CVS symptoms. This quantitative cross-sectional study aimed to identify factors associated with Computer Vision Syndrome among Public Health students at Universitas Muhammadiyah Surakarta. The sample consisted of students from the classes of 2022, 2023, and 2024, using a purposive proportional sampling method with a total of 230 people. This research used the Computer Vision Syndrome Questionnaire (CVS-Q) as an instrument and found that 73,5% of Public Health students suffered from CVS. The Chi-Square test showed a relationship between refractive errors (p=<0,001), use of glasses (p=<0,001; OR = 4,1), duration of laptop use (p=<0,001), and viewing distance from the laptop (p=0,017; OR = 0,46) with CVS. In this study, contact lens use was not associated with CVS (p=0,360). This study suggests that effective prevention and control measures should be developed to decrease the prevalence of Computer Vision Syndrome (CVS) among these undergraduate students, especially during their academic period.